Influence of Body Mass Index (BMI), Age and Gender on Stages of Varicose Vein in Newly Diagnosed Cases Following Screening Doppler in Outpatient Clinic - Shrestha, B.; Karmacharya, R.M. (Kathmandu University Medical Journal, 2020)
Background Varicose vein is one of the most common venous diseases which affect superficial veins especially of lower limb. This disease is characterized by prominent dilated veins, feeling of heaviness, itchiness, pigmentation, ulceration depending upon the stage of the disease. Objective This study was conducted to know how Body Mass Index, Age and Gender influence staging of varicose veins in our context. Method This is a cross sectional hospital based study conducted at Dhulikhel Hospital, Kathmandu University Hospital from April 2018 to March 2019. Patients with signs and symptoms of varicose vein were included in the study. Informed consent was taken from each patient and data collection done by filling the proforma. Result This study comprised 135 lower limbs with varicose vein from 108 patients. Male:Female ratio was 1.4:1. Mean age of patients was 44.47±12.65 (17-81) years. Significant correlation was found between increasing age and progression in Clinical staging of Varicose vein according to Clinical classification (p<0.05). Mean Great Saphenous Vein diameter at knee was found significantly higher in patients with more than five years of symptoms Mean Body Mass Index was not very different in different Clinical stage of Varicose veins. Conclusion This study showed that the Clinical Staging of Clinical Etiological Anatomical and Pathophysiological classification of varicose vein is significantly related to age. The mean diameter of Great Saphenous Vein at the level of Knee is significantly related to the duration of symptoms. However, the influence of Body Mass Index and gender on stages of varicose vein could not be established.